Menakar Keterlibatan Dokter dalam Pelaksanaan Tindakan Kebiri Kimia bagi Pelaku Kekerasan seksual terhadap Anak - Kodrat Alam (Unissula, 2020)
The involvement of forensic doctors in the criminal justice process places doctors as one of the professions who have an important role and assistance in every stage of investigation, investigation, prosecution and evidence in court. The purpose of this study was to understand the scope of the role and assistance of doctors in the criminal justice process, as well as to examine the regulations on child protection in regulating the involvement of doctors in chemical castration. The research method used is normative juridical. Professional organizations reject the involvement of doctors in the implementation of chemical castration because it is against the code of ethics and medical oath. The regulation of the role and assistance of forensic doctors in principle places forensic doctors as experts in the field of judicial medicine whose opinions and expertise can be requested to prove the occurrence of criminal acts involving crimes against body and life.